ANALISIS PERHITUNGAN HARGA POKOK PENJUALAN PADA UMKM USAHA KERUPUK RAMBAK MENGGUNAKAN METODE FULL COSTING DAN METODE VARIABEL COSTING DI KECAMATAN TANON KABUPATEN SRAGEN - Haryanto , Wawan (Jurnal Akuntansi, Keuangan dan Teknologi Informasi Akuntansi, 2024)
To determine the right selling price, the company must first know the cost price to be sold. The company's production results are influenced by the procurement of raw materials, labor and factory overhead costs. Determining the basic price and grouping costs is the most important thing in the company, so that overcosting or undercosting does not occur. This research aims to determine the application of determining the cost of production using the full costing method, in the rambak cracker business using the full costing method and the variable costing method. The conclusion of the research using the variable costing method is IDR 14,972.5 and for the full costing variable it is IDR 19,282.5. The calculation of the cost of production used for the sales break-even point using variable costing and full costing has a difference of IDR 4,310 with the same amount of production produced. namely 1 ton in one production. For producers, they can use the full costing method calculation, providing notes related to raw materials and labor as well as BOP and determining the HPP of the product. They can determine a selling price that is profitable for the producer. Research provides suggestions for investing as a tool for production. The government provides communication channels to consumers regarding products made to producers. Keywords: Cost of Goods Sold, UMKM, Crackers, Rambak, Full Costing